PENGARUH BRAND AWARENESS TERHADAP MINAT KUNJUNGAN WISATAWAN DI ALUN-ALUN KOTA DEPOK - Zahra, Thalia Ghevira; Bellia, Fristi; Guntawan, Akhmad (LPPM Politeknik Pajajaran ICB Bandung, 2023)
The tourism sector has a crucial role in driving economic growth and regional development. A place that has potential to be developed as a tourist destination is the Depok City Square. Although it has been equipped with adequate public facilities, the number of people visiting the location still shows inconsistency. This study aims to determine the effect of brand awareness on tourist interest in visiting the Depok City Square. This study uses a descriptive quantitative method using a survey approach. 379 respondents were selected through a simple random sampling technique from population of residents who had visited the Depok City Square. Data collection was carried out by distributing questionnaires and analyzed with the help of statistical software. the results of the analysis showed that the significance value was 0.000 (<0.05) and the coefficient value of the relationship was 0.459. Thus, it can be concluded that H0 is rejected and H1 is accepted, which means there is a significant impact and a fairly strong and unidirectional correlation between brand awareness and tourist interest in visiting the Depok City Square. Keywords: Brand Awareness; Visit Interest; Tourist Destination